'SALAMELICA': NEW THOUGHTS ON VOLPINO AND HIS ARIA IN ACT III OF LO SPEZIALE. (March 2020) - MAYES, CATHERINE
Abstract : Recently, as I was doing research for a project on eighteenth-century dances, I came across the following entry in Charles Compan's Dictionnaire de danse (1787): Salamalec. Salut à la Turque, qui signifie, Dieu vous garde . On s'est servi longtems à Paris de cette expression, pour saluer une personne en buvant à sa santé. Salamalec, ou, comme prononcent les Turcs, Selamalec, n'est pas seulement une salutation des Turcs, mais encore des Arabes, & même de tous les peuples Mahométans. Salamalec. Turkish greeting meaning 'May God keep you'. This expression has long been used in Paris as a toast when drinking to someone's health. 'Salamalec', or as the Turks pronounce it, 'Selamalec', is not only a greeting of the Turks, but of Arabs and even of all Muslim peoples.